An input-output analysis of mineral processing in economic development : case studies of copper in Zambia and phosphates in Morocco - 246923 Bocoum, Brigitte Marie Khadidja (Ann Arbor, MI : UMI, 1992)
Thesis (PhD) - West Virginia University, 1992